2011
DOI: 10.1103/physrevb.83.159905
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Fidelity susceptibility, scaling, and universality in quantum critical phenomena [Phys. Rev. B77, 245109 (2008)]

Abstract: In the paper, 1 the rescaled function (χ m − χ )/χ [Eq. (8)] was defined as a function of L ν (λ − λ m ) and the exponent ν was identified as the critical exponent of the correlation length. In fact, the exponent of L should have been written as 1/ν in order for ν to be the critical exponent of the correlation length. Accordingly, the corresponding values of ν, including those obtained in Refs. 2-4, should be changed to 1/ν. In particular, scaling relations such as Eq. (9) should read(1)[Eq. (9) has d = 1 subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 4 publications
5
88
0
Order By: Relevance
“…Recently, the fidelity, a concept in quantum information theory, has been extensively used to identify the QPTs in various many-body systems from the perspective of the groundstate wave functions [22][23][24][25][26][27][28][29]. In a mathematical sense, the fidelity is the overlap between two ground states where the transition parameters deviate slightly.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the fidelity, a concept in quantum information theory, has been extensively used to identify the QPTs in various many-body systems from the perspective of the groundstate wave functions [22][23][24][25][26][27][28][29]. In a mathematical sense, the fidelity is the overlap between two ground states where the transition parameters deviate slightly.…”
Section: Resultsmentioning
confidence: 99%
“…Kosterlitz-Thouless transitions, laking a local order parameter, were successfully detected calculating the fidelity susceptibility of the XXZ spin chain 22,23 . Many other systems were also studied such as the onedimensional Hubbard model 24,25 , spin-1/2 particles on a torus 26 , the toric code model and the quantum eightvertex model 27 , the spin honeycomb Kitaev model [28][29][30][31][32] , as well as other spin systems 33,34 . In the thermodynamic limit, the ground state of a local Hamiltonian having a finite energy gap is characterised by short range correlations of local observables.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the intrinsic relation between the GS fidelity and the derivative of GS energy has been studied and it is observed that they play a equivalent role in identifying the QPTs [22]. Since no a priori knowledge of the order parameter is needed, it may be a great advantage to study the scaling behavior of FS to characterize the universality in quantum critical phenomena [21].…”
Section: Introductionmentioning
confidence: 99%